Doses of N, P and K in the cultivation of eucalyptus in soil originally under Cerrado Vegetation - De Niro Gazola, Rodolfo [UNESP]; Buzetti, Salatiér [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Dinalli, Raíssa Pereira [UNESP]; De Moraes, Mario Luiz Teixeira [UNESP]; De Souza Celestrino, Thiago [UNESP]; Da Silva, Paulo Henrique Müller; Dupas, Elisângela [UNESP] (Universidade Estadual de Londrina, 2015)
Many eucalyptus plantations in Brazil are in areas of soil with low fertility, with little phosphorous (P) and potassium (K) availability and with low organic matter (OM) content, resulting in a low supply of nutrients to plants, directly reflected in reduced yield. Thus, our objective was to evaluate the effects of nitrogen (N), P and K fertilization on the growth of eucalyptus plants, with the aim of achieving nutritional balance and high yield. The experiment was conducted on Renascença Farm, an agricultural property administered by Cargill Agrícola S.A., located in the city of Três Lagoas, Mato Grosso do Sul state, Brazil. The experimental design consisted of randomized blocks with ten treatments and five replicates. The treatments were composed of doses of N (0, 70, 105 and 140 kg ha-1), doses of P (0, 40, 70 and 100 kg ha-1 of P2O5) and doses of K (0, 90, 135 and 180 kg ha-1 of K2O). The doses of N and K were applied at planting and as top dressing, and the doses of P were applied only at planting. The diameter at breast height (DBH), plant height and timber volume with bark were assessed, and the concentrations of macronutrients in the leaves were determined. DBH and volume were positively affected by N fertilization, and eucalyptus growth in DBH, height and volume increased with P and K fertilization. The maximum yield of eucalyptus at 21 months of age was obtained with the application of 71 kg ha-1 of N, 100 kg ha-1 of P2O5 and 125 kg ha-1 of K2O. The concentrations of macronutrients were adequate even in the absence of the application of N, P and K. With increasing doses of K, there was an increase in leaf concentrations of K and a decrease in those of calcium and magnesium.
Keywords: Eucalyptus; Fertilization; Macronutrients; Nutritional state of plants